Comparison of Serum Electrolyte Levels in Patients Who Presented at The Emergency Room of Rajavithi Hospital with Atrial Fibrillation with Rapid Ventricular Response and those Who Had Normal Sinus Rhythm - Piyanuttapull, Sumitra; Waenlor, Chalita (International Journal of Innovative Research in Medical Science, 2016)
Background: - Atrial fibrillation (AF) is a form of cardiac arrhythmia which is frequently encountered in emergency rooms, and atrial fibrillation with rapid ventricular response, a condition which increases the likelihood of morbidity and mortality, is especially common. There are many causes of AF, and it may be associated with electrolyte imbalance. This study compared serum electrolyte levels in patients who presented at the Emergency Room of Rajavithi Hospital with atrial fibrillation with rapid ventricular response and in those who had normal sinus rhythm. Objectives: - We compared serum electrolyte levels in patients in two groups: subjects with atrial fibrillation with rapid ventricular response and those with normal sinus rhythm. We also studied other precipitating factors that may be associated with atrial fibrillation with rapid ventricular response. Method: - We studied 266 patients who came to the Emergency Room of Rajavithi Hospital between 1 October 2014 and 30 September 2015. Of these, 56 were diagnosed as having atrial fibrillation with rapid ventricular response, and the remaining 210 were diagnosed with normal sinus rhythm. The serum electrolyte levels of the two groups were compared using a retrospective descriptive study. Data were collected from OPD cards, and statistical analysis was performed using SPSS program version 17 in terms of percentages, means and standard deviation. Results: - The patients who presented with atrial fibrillation with rapid ventricular response were significantly older than those in the normal group (p-value=0.004, OR1.03, 95%CI1.01-1.05), and serum phosphorus levels were higher in the AF with RVR group than in the normal group (p-value<0.001, OR2.03, 95%CI1.37-3.00). The group of AF with RVR patients had average phosphorous levels of 3.55±0.93 compared with 3.08±0.75 in the NSR group, while serum magnesium levels were lower in the AF with RVR group than in patients in the normal group (p-value=0.003, OR0.19, 95%CI0.06-0.57). The group of AF with RVR patients had average magnesium levels of 1.92±0.36 compared with 2.06±0.30 in the NSR group. Conclusion: - Patients who presented at the Emergency Room with atrial fibrillation with rapid ventricular response had higher serum phosphorus levels and lower serum magnesium levels than those with normal sinus rhythm.